Cost Effectiveness Of Quadrivalent Influenza Vaccines In The Elderly Population Of Malaysia - Syed MohamedAljunid; Nur Syazana MadTahir; Aniza Ismail; Aznida FirzahAbdulAziz; Amirah Azzeri; S.A. Zafrah; Azimatun NoorAizuddin (Springer Nature, 2024)
Indexed by Scopus/ERA